Literasi Keuangan dan Inklusi Keuangan yang Tepat: Membentuk UMKM yang Sustainable (Studi Kasus pada Resto Nasgor Jawa Pak Sam Brangsong) - Rofi’I Rofi’I; Gilang Kharisma Putra (Jurnal Publikasi Manajemen Informatika, 2024)
This research aims to find out how big the role and functions of Financial Literacy and Financial Inclusion are in MSMEs in the Brangsong sub-district area. This research uses a sample of one of the MSMEs in the Brangsong sub-district, namely Resto Nasgor Jawa Pak Sam Brangsong which has been established since 2017 which has been proven to be sustainable to this day. Until now, many MSMEs in the Brangsong sub-district area are still in decline and have not been able to recover as before due to the Covid-19 pandemic disaster. The results of research on the UMKM Resto Nasgor Jawa Pak Sam Brangsong show that the application of Financial Literacy and proper implementation of Financial Inclusion plays a very important role in the survival of an UMKM, as proven by the proper implementation of Financial Literacy and Inclusion can make Resto Nasgor Jawa Pak Sam Brangsong Sustainable and able to pass during the pandemic well.